Images of Indian Woman in Shashi Deshpande’s That Long Silence—Stereotypes, Myths and Realities: Representation of Indian Woman in Shashi Deshpande's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Indian English Fiction portrays a lucid image of our Culture and Society. The consistent bondage to tradition has ignited an oppression and injustice against woman. Indian woman novelists have acknowledged the value of themselves by providing a valuable contribution to Indian English Literature. Shashi Deshpande is one among the prominent contemporary women writers in India. She began her career in 1970’s and she created characters that are a replication of Indian middle class women. In the novels of Shashi Deshpande one is able to recognize credible female characters with flesh and blood. She presents the authentic life of a women and not shadowy abstractions. The heroines of the novelist are typical example of stereotypical virtues of Indian women, who explode the myth of man’s superiority. The novelist is successful in creating real life characters that live their day today life she has not merely created women puppets to act to the scene.